Fluorescence Assay for Evaluating Microbicidal Activity of Hand Antiseptics - Lopez-Gigosos, Rosa M. (Appl Environ Microbiol, 2015)
We developed a fluorescent β-d-glucuronidase activity (BGA)-based assay for detecting and quantifying Escherichia coli in samples to assess the biocide efficacy of hand antiseptics. The fluorescence level is proportional to the number of viable E. coli organisms present. We compared our assay results to those of the E. coli plate count method specified by the European standard for testing hygienic hand rub disinfectant products (EN1500). The plate count method requires excessive handling and materials and is not valid if the number of organisms per plate is too low or high for counting in many of the samples. We optimized the fluorescent assay based on the cleavage of 4-methylumbelliferyl-β-d-glucuronide by adding 4-nitrophenyl-β-d-glucuronide, a nonfluorogenic BGA substrate, to induce glucuronidase activity and reduce assay time. Furthermore, our method can be automated and eliminates the need for multiple dilutions. Fluorescence was temporally monitored, and the time required to reach a specific value of fluorescence was correlated with the initial number of viable E. coli organisms on the samples. There was a positive correlation (P < 0.05) with a high correlation coefficient (R(2) = 0.82) between the E. coli counts by plate count and fluorescence methods. Reported effects in fluorescent BGA were compared to the EN1500 plate count method with five hand disinfectants. We found our method more advantageous, because it was as sensitive as the EN1500 method, requires less time to complete, and is less expensive and less laborious than conventional plating techniques.